Hospital volume following major surgery for gastric cancer determines in-hospital mortality rate and failure to rescue: a nation-wide study based on German billing data (2009-2017) - Diers, Johannes; Baum, Philip; Wagner, J. C.; Matthes, Harald; Pietryga, Sebastian; Baumann, Nikolas; Uttinger, Konstantin L.; Germer, Christoph-Thomas; Wiegering, Armin (Gastric cancer, 2021)
For many cancer resections, a hospital volume-outcome relationship exists. The data regarding gastric cancer resection—especially in the western hemisphere—are ambiguous. This study analyzes the impact of gastric cancer surgery caseload per hospital on postoperative mortality and failure to rescue in Germany.